Improving nursing education curriculum as a tool for strengthening the nurse-client relationships in maternal and child healthcare: Insights from a human-centered design study in rural Tanzania - Kahabi Ganka Isangula; Eunice Siaity Pallangyo; Eunice Ndirangu-Mugo (Frontiers Media S.A., 2023)
BackgroundThere are growing evidence of poor nurse-client relationships in maternal and child health (MCH). The nursing curriculum forms an important entry point for strengthening such relationships, consequently improving client satisfaction with nurses' competencies, confidence in the formal healthcare system, healthcare-seeking practices, continuity with care, and MCH outcomes.ObjectiveMCH nurses and clients were invited to design an intervention package (prototype) to improve nurse-client relationships using a human-centered design (HCD) approach.MethodsA multi-step HCD approach was employed to first examine the contributors of poor nurse-client relationships using nine focus group discussions with nurses and clients and 12 key informant interviews with MCH administrators. Then, three meetings were held with 10 nurses, 10 clients, and 10 administrators to co-develop an intervention package to address the identified contributors. The solutions were validated by collecting qualitative information through six focus groups with nurses and MCH clients who were not involved in the initial HCD stages. Finally, refinement and adaptation meetings were held with 15 nurses, 15 clients, and 10 administrators. The data were managed with NVivo 12 software and analyzed thematically.ResultsNursing curriculum challenges contributing to poor nurse-client relationships in MCH care included inadequate content on nurse-client relationships specifically topics of customer care, communication skills, and patient-centered care; an inadequate practice on communication skills within nursing schools; and the absence of specific trainers on interpersonal relationships. Consequently, improving the nursing curriculum was one of the interventions proposed during the co-design and rated by participants as highly acceptable during validation and refinement meetings. Suggested improvements to the curriculum included increasing hours and credits on communication skills and patient-centered care, including customer care courses in the curriculum and creating a friendly learning environment for clinical practice on strengthening interpersonal relationships.ConclusionImproving the nursing curriculum was considered by nurses and clients as one of the acceptable interventions to strengthen nurse-client relations in MCH care in rural Tanzania. Nursing education policy and curriculum developers need to ensure the curriculum facilitates the development of much-needed interpersonal skills among nursing graduates for them to have positive therapeutic interactions with their clients.